A Study on the Effect of Organizational Justice and Commitment on the Organizational Citizenship Behavior - Bazgir, Afhsin; Vahdati, Hojjat; Nejad, Seyed Hadi Mousavi (UI Scholars Hub, 2018)
In today's research it has been confirmed that organizational citizenship behavior has a significant effect on the performance of employees and organization. Therefore, this research investigating factors affecting organizational citizenship behavior including organizational justice and organizational commitment. The present study is an applied research in terms of purpose, a causal-effect in terms of research nature and approach, a descriptive survey in terms of data collection and a quantitative in terms of data type. The research population includes 124 employees and middle managers in Lorestan who were surveyed by census sampling method. The results of path analysis indicate that organizational justice directly and indirectly (through the mediator role of organizational commitment) has a positive and significant effect on organizational citizenship behavior.